AB0040 Role of Innate Immunity in the Pathogenesis of Anca-Associated Vasculitis. (10th June 2014) - Gattamelata, A.; Peruzzi, G.; Scrivo, R.; Priori, R.; Morrone, S.; Santoni, A.; Valesini, G.
Abstract : Background: Natural killer (NK) cells represent one of the main effectors of the innate immune response. Toll-like receptors (TLRs) are a family of evolutionally-conserved host defense mechanism against pathogens. Recent evidence shows an increase in the expression of TLR2 and TLR9 on NK cells of patients with ANCA-associated vasculitis (AAV) compared with healthy controls (HC) 1 . This observation is of great interest considering that infections have been implicated in the pathogenesis of these diseases. Objectives: To characterize peripheral NK cells in patients with AAV, assessing their number, phenotype, and functional status, in order to investigate their role in the pathogenesis of these diseases. Methods: We enrolled 19 patients with AAV [8 F, 11 M; mean age 60.2 years (range 41-75)] according to the criteria of Chapel Hill 2 and 17 HC matched for age and sex with the patients. After obtaining informed consent, clinical data were collected and blood draw was performed. Peripheral blood mononuclear cells (PBMCs) were isolated from heparinized blood by Lymphoprep gradient centrifugation. NK cells (CD3-CD56+) were evaluated by multi-parameter flow cytometry, distinguishing between cytotoxic CD56 dim and immunoregulatory CD56 bright NK cells, as well as memory NK cells (CD3-CD56+CD57+) and NCR + ILC3 also known as NK-22 cells. The expression of TLR2 and TLR9 was evaluated on all of these cells. Finally, NK cells were isolated by magnetic separation to assess the state of activation through the expression of intracellular IFN-g following in vitro incubation with TLR2 (Pam3CSK4) or TLR9 (CpG ODN) ligands. Results: No significant differences were found in the number and percentages of NK cells between patients and HC (12.9% vs 9.4%). The percentages of CD56 dim and CD56 bright NK cells in AAV patients and HC (83.4% vs 93.5% and 6.9% vs 7.2%, respectively) and those of memory NK cells and NCR + ILC3 CCR6+/NKp44+ (64.3% vs 63.6% and 0.44% vs 0.47%, respectively) were comparable. The expression of TLR2 on NK cells was significantly higher in patients compared to HC (22.6% vs 11.3%; p=0.02), while no differences in the percentage of TLR9 expression (38.5% vs 33.3%) were observed. Likewise, in the memory NK cell subset, the expression of TLR2 was significantly decreased in patients with respect to HC (13% vs 23.1%; p=0.01), while the expression of TLR9 (53.8% vs 54.17) was comparable. Interestingly, the stimulation of purified NK cells with TLR9 ligand induced a significant intracellular production of IFN-g in patients compared to HC (10.4% vs 2.7%; p=0.002), whilst no effect was observed following incubation with TLR2 ligand. No correlation was found among the NK cell data and clinical parameters of the patients. Conclusions: The significant reduction of TLR2 expression on total NK cells and the memory subset in patients with respect to HC suggests that TLR2 may be down-regulated in AAV patients. The increased production of IFN-g after stimulation with the ligand of TLR9 demonstrates a state of NK activation in AAV patients following this pathway. Hence, TLR2 and TLR9 may be involved in the pathogenesis of these diseases, strengthening the possibility that infections may promote their onset and/or exacerbations. References: Tadema H et al. PLoS One 2011;6(9):e24315 Jennette JC et al. Arthritis Rheum 1994; 37: 187-92 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5161